In vitro and in vivo investigation of bisphosphonate‐loaded hydroxyapatite particles for peri‐implant bone augmentation. (9th November 2015) - Kettenberger, Ulrike; Luginbuehl, Vera; Procter, Philip; Pioletti, Dominique P.
Abstract: Locally applied bisphosphonates, such as zoledronate, have been shown in several studies to inhibit peri‐implant bone resorption and recently to enhance peri‐implant bone formation. Studies have also demonstrated positive effects of hydroxyapatite (HA) particles on peri‐implant bone regeneration and an enhancement of the anti‐resorptive effect of bisphosphonates in the presence of calcium. In the present study, both hydroxyapatite nanoparticles (nHA) and zoledronate were combined to achieve a strong reinforcing effect on peri‐implant bone. The nHA–zoledronate combination was first investigated in vitro with a pre‐osteoclastic cell assay (RAW 264.7) and then in vivo in a rat model of postmenopausal osteoporosis. The in vitro study confirmed that the inhibitory effect of zoledronate on murine osteoclast precursor cells was enhanced by loading the drug on nHA. For the in vivo investigation, either zoledronate‐loaded or pure nHA were integrated in hyaluronic acid hydrogel. The gels were injected in screw holes that had been predrilled in rat femoral condyles before the insertion of miniature screws. Micro‐CT‐based dynamic histomorphometry and histology revealed an unexpected rapid mineralization of the hydrogel in vivo through formation of granules, which served as scaffold for new bone formation. The delivery of zoledronate‐loaded nHA further inhibited a degradation of the mineralized hydrogel as well as a resorption of the peri‐implant bone as effectively as unbound zoledronate. Hyaluronic acid with zoledronate‐loaded nHA, thanks to its dual effect on inducing a rapid mineralization and preventing resorption, is a promising versatile material for bone repair and augmentation. Copyright © 2015 John Wiley & Sons, Ltd.